Compression therapy for ulcers: The science and the art - Gogia, Shashi B.; Gogia, Arun R. (Indian Journal of Plastic Surgery, 2012)
Introduction: Chronic ulcers are characterized by being resistant to all forms of treatment. Recent improvement in compression techniques, notably use of multilayer bandaging has created a need for a re-look into it′s use. Materials and Methods: The authors present two case reports of successful management of chronic ulcers using compression through bandaging where all other forms of treatment had failed. This is followed by a review of literature based on previous articles as well as more recent ones found through Pubmed. Conclusion: It is suggested that, at least in India, compression through proper multilayer bandaging, should be a choice far higher in the treatment ladder than so previously. However, if the technique is improper, it may be harmful so the option is to be exercised with care and only by those who have received adequate training. The need of a team approach, and alongside, wider introduction of more and better training facilities for therapists and nurses is underlined.
Keywords: Chronic ulcers; compression therapy; lymphoedema; multilayer bandaging